(untitled) - Lipsett, Roger (Boston, 1989)
The objective was to significantly enhance operating performance and circuit density for Very Large Scale Integration (VLSI) silicon chips. The U. S. Government realized that in order for contractors to be able to work together to develop VLSI products, to document the resulting designs, to be able to reuse the designs in future products, and to efficiently upgrade existing designs, they needed a common communication medium for the design data. They wanted the design descriptions to be computer readable and executable. They also recognized that with the high densities envisioned for the U. S. Government's Very High Speed Integrated Circuit (VHSIC) chips and the large systems required in future procurements, a means of streamlining the design process and managing the large volumes of design data was required. Thus was born the concept of a standard hardware design and description language to solve all of these problems.
Keywords: Computer input-output equipment,Thiết bị đầu vào máy tính; Computer simulation,Trình mô phỏng